Cultural Persistence as Behavior Towards Risk: Evidence from the North Carolina Cherokees, 1850-1880 - Gregg, Matthew T. (Journal of Income Distribution®, 2009)
Can economic theory help explain the persistence of a cultural enclave among the Cherokee Indians living in North Carolina during the nineteenth century? To date, Fogelson and Kutsche (1961) and Finger (1984) have identified the continuation of a communal, labor-sharing, agricultural institution called the gadugi as an example of Cherokee agency during a period of substantial upheaval. I contribute to the historiography on ancestral labor traditions by adopting Kimball’s (1988) framework on the function of farming cooperatives to test whether this arrangement sprung up as a form of insurance against the idiosyncratic risk inherent in southern agriculture. Data collected from the 1850-1880 manuscript census returns on North Carolina Cherokee farms are used to compute the variance of household self-sufficiency, which appears substantial enough to warrant a non-market mechanism to pool risk.